TAX LIABILITY ARRANGEMENT OF INTERNATIONAL E-COMMERCE IN INDONESIA - Sinaga, Henry Dianto Pardamean; Samekto, F. X. Adji; Emirzon, Joni (Faculty of Law, Universitas Diponegoro, 2023)
International e-commerce has created challenges in terms of tax liability, referred to the study by Google-Temasek-Bain revealed that the combination of e-commerce had reached USD40 billion. Based on normative juridical method using new institutionalism theory, two conclusions are generated. First, the prevailing laws in Indonesia do not yet have a lex specialist that regulates tax liability regarding international e-commerce transactions. Second, it is important and urgent to reformulate secondary liability in tax laws that must cover the elements, exclusions, and standards. Reformulation of tax secondary liability of international e-commerce should be extended to overseas and domestic marketplaces, and social media, including general provisions and procedures, billing, mechanisms for warning and terminating access and normalization, as well as tax sanctions (administrative and criminal).